Iatrogenic Rupture Uterus with Bowel Prolapse – Missmanaged Third Stage of Labour (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
We present a case of mismanaged 3rd stage of labour by untrained dai who delivered the patient by injudicious administration of uterotoric drug and tried to remove the placenta manually with excavation of the small intestine through vagina. Every women present a unique challenge during her pregnancy and delivery period, unfortunately a significant number will have medical and surgical problems which will complicate their pregnancy and puerperal period, develop such serious condition that the lives of both mother and their unborn baby will be threatened. The aim of this case presentation are to ensure the ANC for every women and facilitate to make informed decision concerning where they will be seen, who will undertake the case, which screening test to be done, where they plan to give birth and where she will achieve full facility for safe delivery. These helps to prevent the catastrophic complications.Bangladesh J Obstet Gynaecol, 2017; Vol. 32(2) : 124-127